Development of a Tourism Mobile Application Using Linear Search Algorithm Linked to Cloud-based NoSQL Document Database - Peruda Jr., Sergio R.; Samaniego Jr., Leonardo A.; Brucal, Stanley Glenn E.; Yong, Einstein D.; De Jesus, Luigi Carlo M.; Juguilon, Prince Carlo P.; Ruedas, Reister L.; Sagabaen, Giomar Dave C.; Torio, Arnel E. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – The researchers planned to develop a secure tourism mobile application that acts as a digital guide to help tourists navigate the city. It has features that answer frequently asked questions by tourists while traveling, as well as security features that are required. Method – The JavaScript and React Native framework platforms were used to create the mobile application. The application is designed to protect user information and itself by utilizing Firestore and NoSQL Realtime databases. It is also capable of restricting access to unregistered accounts via Firebase authentication, verifying real users via OTPs, masking critical data via obfuscation, and detecting or blocking devices with an unusual number of requests. Results – The testing results showed that the system was fully functional, with a score of 100% when the major modules were tested. Similarly, after passing all security tests, the application received a 100% system security rating and an average of 4.63 in user-friendliness surveys. Conclusion – The developed system is a fully functional where all necessary functions are met. In terms of system security, the system passed test cases pertaining to malicious access or attacks. The developed system is simple to use, with a user-friendliness rating of 4.63. The identified rating was based on a survey of people in cities surrounding Makati. Recommendations –Some aspects of the project that could be improved is the inclusion of travel planner and weather forecast to provide more control over tour customization, considering interactive and embedded map when doing the route-mapping for a specific accommodation or historical site, and adding a hotline for tourism office without any charges. Research Implications – This application can be cascaded to all Local Government Unit to promote tourism. This application benefits the Tourism Office in the Local Government Unit by providing a new and convenient approach to tourism. As a result, the city's tourist-worthy locations and activities received the exposure and recognition and generated more revenue.